Lilin Kencur (Kaempferia galanga L.) Dengan Variasi Bentuk Sebagai Farmakoterapi - Nikmah, Dewi Fitrotun; Chotimah, Nurul; Rosidah, Siti; Sukarya, Nurdin Kurniawan; Wachidah, Kurnia (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Â Kaempferia galanga Linn. (Zingiberaceae) is indigenous to tropical Asia, where it is commonly used in traditional medicine. This herb has broad-spectrum pharmacological and biological activities including vasorelaxant active. Volatile oil isolated from K. galanga is found to be responsible for the pharmacological actions. Investigations stated the inhalation of K. galanga volatile oil showed sedative effect at certain doses. The findings suggested K. galanga can be one of the promising candidates for aromatherapy. Therefore, this program used K. galanga as ingredients in the production of pharmacotheraphy candle in various shapes and colors. Aromatheraphy candle will release the unique fragrance which has pharmacotheraphy effect, when it is burned. The inhalation of fragrance can be used as a drug replacement to treat patients suffering insomnia. It will give relaxation effect. Other benefit, the fragrance can also repel insects. Innovation of pharmacotheraphy candle with various color and shape is expected to optimize the use ofK. galanga as natural medicine. It is also expected in reducing the use of synthetic chemical drugs that cause dependence. Keywords : candle, Kaempferia galanga L.,pharmacotheraphy,sedative, volatile oil